Enhanced Photon Harvesting in Wedge Tandem Solar Cell. Issue 1 (27th November 2022) - Chamoli, Sandeep Kumar; Singh, Subhash; Guo, Chunlei; Li, Wei
Abstract: Light‐trapping elements play an important role in solar cells to enhance their light‐harvesting efficiency. Pyramidal‐shaped nano‐microstructures and gradient metasurfaces are mostly used as light‐trapping elements in solar cells. There is, however, one major concern with nanostructured solar cells: a larger surface area resulting in a larger surface recombination loss. In this article, a novel thin‐film wedge tandem‐solar cell made of perovskites and silicon is designed where the bottom cell itself works as a light‐trapping element. Optical and electrical simulations are performed to estimate performance metrics of the wedge tandem‐solar cell and compare with typically used unpatterned planar tandem‐solar cell. In terms of optical and electrical performance, wedge geometry outperforms planar geometry and shows 17.18% higher efficiency. Compared to a typical planar tandem cell, such a design can lead to thin and low‐weight tandem solar cells, which can be very useful in space applications. The proposed design can be fabricated using an optimized electrospray deposition process. Abstract : Article compares the optical and electrical performance of wedge tandem cells and typically used planar tandem cells. In the wedge tandem cell, light trapping can enhance photon harvesting due to the wedge shape. An array of unit cells is shown in the zoomed view. The tracing cartoons show a plane and wedge type of cell.